Mineral trioxide aggregate as a pulpotomy agent in immature teeth:Long-term case report - Subay, Rustem Kemal; Ilhan, Banu; Ulukapi, Hasmet (European Journal of Dentistry, 2013)
This case report aimed to present the long-term clinical performance of mineral trioxide aggregate (MTA) pulpotomies in immature permanent teeth. Four patients with complicated crown fractures of five maxillary immature central incisor teeth were treated with pulpotomy using gray MTA. An immature mandibular first molar showing signs of reversible pulpitis that was exposed mechanically during cavity preparation was also treated with MTA pulpotomy. Four of the 6 immature teeth were diagnosed vitally with complete root maturation and with the presence of dentin bridges after 55 months (mean time of follow-ups). MTA pulpotomy was assessed unsuccessfully in two fractured central incisors. Severe discoloration in the crowns was present in all 6 cases. MTA may induce pulp healing with dentin bridge formation and prevent necrosis at long-term periods in most of the pulpotomy cases. However, discoloration following MTA pulpotomy is a significant clinical complication. (Eur J Dent 2013;7:133-138)
Keywords: Immature teeth; mineral trioxide aggregate; pulpotomy